PENGEMBANGAN MEDIA PEMBELEJARAN KIMIA MENGGUNAKAN PROGRAM PREZI PADA POKOK BAHASAN STRUKTUR ATOM - Nurhayati Sihombing; Betty Holiwarni; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is a Research and Development (R & D). The development process has been done with reference to ADDIE model with steps of Analyze, Design, Development, Implementation, Evaluation. Research was conducted in FKIP UR. This research aims to obtain the learning media chemistry using by prezi on subject of the atomic structure. The research and development with ADDIE model was conducted only until Development step, because the purpose of this research was limited to develop and produce a feasiblity the learning media chemistry using by prezi to be implemented based on validator assessment. Feasibility of the learning media chemistry using by prezi was evaluated from feasibility of the design, pedagogy,content, ease of use. Of the learning media chemistry validation result obtained an average value as 86,31% which showed that learning media chemistry which developed was feasiblity. Means, learning media chemistry using by prezi oriented scientific approach on the subject of the atomic structure that was developed, suitable to be used in learning process.Keyword : ADDIE Model, Learning Media Chemistry Using By Prezi, And Atomic Structure